TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTEK HADIAH WADI’AH YAD ADH-DHOMANAH: Stadi Kasus Pada Produk Sajadah Di KSPP. Syariah BMT NU Jawa Timur Cabang Pujer Kab. Bondowoso - Wasilah Wasilah (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2021)
How is the practice of giving Wadi'ah yad adh dhomanah prizes to SAJADAH products at the KSPP Syariah BMT NU East Java, Pujer Branch, Kab. Bondowoso? 2. What is the Review of Sharia Economic Law on the Practice of Giving Wadi'ah yad adh dhomanah gifts to KSPP SAJADAH products. SYARIAH BMT NU East Java Pujer branch Kab. Bondowoso. The research method used is a qualitative method through data collection techniques in the form of interviews and documentation. The analysis technique uses a descriptive analysis method using a deductive mindset. The practice of giving Wadi'ah yad adh dhomanah gifts to SAJADAH products at KSPP Syariah BMT NU East Java Pujer Branch Kab. Bondowoso is not in accordance with the existing theory because the gift or bonus has been promised at the beginning. Review of Sharia Economic Law on the Practice of Giving Wadi'ah yad adh dhomanah prizes to KSPP SAJADAH products. SYARIAH BMT NU East Java Pujer branch Kab. Bondowoso in its implementation is appropriate based on the pillars of the wadi'ah contract. While the conditions related to the goods to be presented have not met the requirements because the goods were not available at the time the gift was given or when the contract took place.